Seasonal and geographical adaption of two field crickets in China (Orthoptera: Grylloidea: Gryllidae: Gryllinae: Teleogryllus) - He, Zhuqing; Wang, Xiaoyin; Liu, Yuqing; Li, Kai (Zootaxa, 2017)
Crickets of the genus Teleogryllus belong to Gryllidae, Orthoptera. Teleogryllus emma (Ohmachi and Matsumura) and T. occipitalis (Serville) are widely distributed in east Asia, but their distribution and life history have not been reported from China. We studied the seasonal and geographical adaptation by rearing these crickets and measuring specimens. The main results are as follows: T. emma belongs to short-day type, which means nymphs grow rapidly in short day conditions (LD 12:12); T. occipitalis belongs to long-day type, which means nymphs grow rapidly in long day conditions (LD 16:8). The nymphal growth rate accelerates with the increase of temperature by comparing their nymph developmental period at 25 and 30OC. T. emma is mainly distributed in the north of the Yangtze River, while T. occipitalis in the south of it. The body size decreases with the increase of latitude in both species, while the relative length of their ovipositor increases.